Microbial diversity and activity in the Nematostella vectensis holobiont: insights from 16S rRNA gene sequencing, isolate genomes, and a pilot-scale survey of gene expression - Har, Jia Y.; Helbig, Tim; Lim, Ju H.; Fernando, Samodha C.; Penn, Kevin; Reitzel, Adam M.; Thompson, Janelle R. (Frontiers in Microbiology, 2015)
We have characterized the molecular and genomic diversity of the microbiota of the starlet sea anemone Nematostella vectensis, a cnidarian model for comparative developmental and functional biology and a year-round inhabitant of temperate salt marshes. Molecular phylogenetic analysis of 16S rRNA gene clone libraries revealed four ribotypes associated with N. vectensis at multiple locations and times. These associates include two novel ribotypes within the ε-Proteobacterial order Campylobacterales and the Spirochetes, respectively, each sharing <85% identity with cultivated strains, and two γ-Proteobacterial ribotypes sharing >99% 16S rRNA identity with Endozoicomonas elysicola and Pseudomonas oleovorans, respectively. Species-specific PCR revealed that these populations persisted in N. vectensis asexually propagated under laboratory conditions. cDNA indicated expression of the Campylobacterales and Endozoicomonas 16S rRNA in anemones from Sippewissett Marsh, MA. A collection of bacteria from laboratory raised N. vectensis was dominated by isolates from P. oleovorans and Rhizobium radiobacter. Isolates from field-collected anemones revealed an association with Limnobacter and Stappia isolates. Genomic DNA sequencing was carried out on 10 cultured bacterial isolates representing field- and laboratory-associates, i.e. Limnobacter spp., Stappia spp., P. oleovorans and R. radiobacter. Genomes contained multiple genes identified as virulence (host-association) factors while S. stellulata and L. thiooxidans genomes revealed pathways for mixotrophic sulfur oxidation. A pilot metatranscriptome of laboratory-raised N. vectensis was compared to the isolate genomes and indicated expression of ORFs from L. thiooxidans with predicted functions of motility, nutrient scavenging (Fe and P), polyhydroxyalkanoate synthesis for carbon storage, and selective permeability (porins). We hypothesize that such activities may mediate acclimation and persistence of bacteria in N. vectensis.